Job Insecurity and Turnover Intention: The Moderating Role of Psychological Capital among Nigerian Employees - Iwueze, Iheanyi; Vaultier , Manuel (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to examine the relationship between job insecurity and turnover intention and to determine whether psychological capital moderates this relationship among employees in Nigeria. Methods and Materials: A descriptive correlational design was employed with a sample of 410 full-time employees from diverse public and private organizations in Nigeria. The sample size was determined using Morgan and Krejcie’s table to ensure adequate statistical power. Data were collected via standardized instruments: the Job Insecurity Scale, the Psychological Capital Questionnaire (PCQ-24), and the Turnover Intention Scale (TIS-6). Statistical analyses were performed using SPSS-27 for descriptive and bivariate correlation analyses and AMOS-21 for Structural Equation Modeling (SEM). Model fit was evaluated using χ²/df, CFI, TLI, GFI, AGFI, and RMSEA indices. Findings: Job insecurity was positively and significantly associated with turnover intention (r = .56, p < .001), while psychological capital was negatively correlated with both job insecurity (r = –.41, p < .001) and turnover intention (r = –.48, p < .001). SEM indicated good model fit (χ² = 124.87, df = 61, χ²/df = 2.05, CFI = .96, TLI = .95, GFI = .94, AGFI = .91, RMSEA = .051). Job insecurity had a strong direct positive effect on turnover intention (β = .53, p < .001), while psychological capital showed a significant negative direct effect (β = –.42, p < .001). The interaction effect was significant (β = –.16, p = .001), confirming that higher psychological capital attenuates the impact of job insecurity on turnover intention. Conclusion: These findings highlight the critical buffering role of psychological capital in reducing turnover intention under job insecurity. Developing employees’ hope, resilience, optimism, and self-efficacy can serve as an effective retention strategy, especially in economically volatile environments.